Mainstreaming Social-Cultural Competencies Through a Religious Moderation Model Based on Local Wisdom - Khamdan, Muh; Wiharyani (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2024)
This research explores strategies for strengthening socio-cultural competence through a religious moderation model based on Indonesian society's local wisdom. Socio-cultural competence is an ability that civil servants must have in the form of awareness to know, accept, and advance the cultural diversity of the Indonesian nation. This paper uses a qualitative research model with document analysis methods based on theoretical aspects, planning, and implementation of socio-cultural regulations. Qualitative methodology provides in-depth insights, combining content and descriptive analysis to process information from various documents. The main material for this research includes documents related to Pancasila values, the commodification of cultural identity, and religious moderation practices based on local wisdom. This article shows that strengthening socio-cultural competence is strongly influenced by planning and implementing policies in cultural promotion work. Therefore, a strengthening strategy is needed that includes respecting differences and fostering a sense of love for the country through a moderation model based on local wisdom.